PENGOBATAN TRADISIONAL PENYAKIT DADA BURUNG PADA MASYARAKAT DESA FRITU KECAMATAN WEDA UTARA KABUPATEN HALMAHERA TENGAH - Verly Ayuni Wangelamo (Universitas Sam Ratulangi, 2023)
Traditional medicine is still widely used in various communities, both in villages and in cities. Knowledge about the use of traditional medicinal plants is the nation's cultural heritage based on knowledge and experience passed down from generation to generation so as to create various medicinal herbs that are characteristic of traditional Indonesian medicine. Medicine is divided into two, namely modern medicine and traditional medicine. Modern medicine usually tends to ignore the spiritual, social and religious aspects of a person. Trust and confidence are an important factor in treatment. While traditional medicine is a method of treatment or treatment using traditional procedures. Both from his knowledge, experience, skills that are passed down from generation to generation based on tradition in an area of society. In the community of Fritu Village, North Weda District, Central Halmahera Regency, there is a unique traditional treatment for pigeon chest disease. The meaning is unique and different from the treatment of other pigeon chest diseases because in the treatment process 4 (four) traditional medicine methods are carried out, namely, first people who suffer from pigeon chest disease by chewing ginger or people in Fritu Village usually call it kunya goraka; Second, the Shaman recites a mantra and blows on the painful part of the chest (pigeon chest); Third, the Shaman attaches the leaves of traditional medicinal herbs to the patient's chest; Fourth, Shamans apply using traditional media tools and plant medicinal materials that are typical according to the local wisdom of the people of Fritu Village. Keywords: local wisdom, folk remedies, pigeon chest disease